2004
DOI: 10.1074/jbc.m408652200
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of Multiple Murine ATP-binding Cassette Transporter G1 mRNAs/Isoforms That Stimulate Cellular Cholesterol Efflux to High Density Lipoprotein

Abstract: The murine Abcg1 gene is reported to consist of 15 exons that encode a single mRNA (herein referred to as Abcg1-a) and protein. We now demonstrate that (i) the murine gene contains two additional coding exons downstream of exon 1, (ii) transcription involves the use of multiple promoters, and (iii) the RNA undergoes alternative splicing reactions. As a result, three mRNAs are expressed that encode three putative protein isoforms that differ at their amino terminus. ABCG1 transcripts are induced in vivo in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 52 publications
6
130
0
1
Order By: Relevance
“…Second, the level of ABCA1 but not ABCG1 mRNA was decreased with IL-1␤ treatment. If LXR is involved, the regulatory pattern of ABCA1 and ABCG1 should be similar (24). Finally, the deletion of the DR4 element from the promoter of ABCA1 did not reverse the effect of IL-1␤.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the level of ABCA1 but not ABCG1 mRNA was decreased with IL-1␤ treatment. If LXR is involved, the regulatory pattern of ABCA1 and ABCG1 should be similar (24). Finally, the deletion of the DR4 element from the promoter of ABCA1 did not reverse the effect of IL-1␤.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Laffitte et al 31) reported that LXR agonist-induced ABCA1 and ABCG1 expressions in macrophages were completely abolished by the deletion of both LXR and LXR . Other studies have shown that the ABCG1 gene is transcriptionally activated by activated LXR through its binding elements 12) . Taken together, the above observations suggest that ABCG1 is regulated via PPAR , both in an LXRdependent and -independent manner, and the LXRindependent effect of PPAR activation on ABCG1 expression could overwhelm the inhibitory effect of LXR knockdown on ABCG1.…”
Section: Discussionmentioning
confidence: 99%
“…LXR and/or PPAR reportedly up-regulated the ATP binding cassette transporters (ABC) A1 9,11) , and ABCG1 12,13) and scavenger receptor class B type (SR-B ) 14) , all of which facilitate cellular cholesterol efflux 12,[15][16][17][18] . The deletion of PPAR 9,19) , LXR 20) , ABCA1 21) , ABCG1 22) , and SR-B 23) in macrophages reportedly accelerates the development of atherosclerosis and treatment with LXR 24) and PPAR 25) ligands inhibits its development; however, it is still not clear whether PPAR -activating ARBs affect the expression of these genes and cholesterol efflux from macrophages, and regulate PPARinducible genes in human cells 26) .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Tangier's disease, a syndrome characterised by low plasma levels of HDL-C and impaired cholesterol efflux, are deficient in ABCA1 [22]. It has recently been reported that other ATP-binding proteins, ABCG1 and ABCG5 [23,24], are involved in the efflux of cholesterol to lipidated HDL particles. Immense interest has been focused on the development of pharmacologic strategies that promote the expression of these transmembrane proteins and thus facilitate reverse cholesterol transport.…”
Section: Hdl Facilitates Reverse Cholesterol Transportmentioning
confidence: 99%